HUBUNGAN ANTARA WAKTU TANAM DENGAN HASIL DAN PROFITABILITAS BUDIDAYA KENTANG (Solanum tuberosum l.) DI CIKAJANG, GARUTRELATIONSHIPS BETWEEN PLANTING TIME AND YIELD AS WELL AS PROFITABILITY OF GROWING POTATO ... - Rakhmat Hanafi Ajis; I Handoko (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2010)
Relationships between planting time and yield as well as profitability of growing potato were investigated in Cikajang, Garut, based on water balance analysis and survey to potato farmers of the area. In general, there were three planting dates namely December-January, April-May and August-September. Yield and profitability of growing potato for planting time of August-September was less compared to the other two planting times due to lack of soil-water availability related to less rainfall as well as its high rainfall variability during dry season (coefficient of variation = 133%). Yields of potato for planting times December-January, April-May and August-September were (21.4 + 3.4), (20.5 + 3.5) and (16.9 + 2.2) tonnes/ha, respectively.Relationships between planting time and yield as well as profitability of growing potato were investigated in Cikajang, Garut, based on water balance analysis and survey to potato farmers of the area. In general, there were three planting dates namely December-January, April-May and August-September. Yield and profitability of growing potato for planting time of August-September was less compared to the other two planting times due to lack of soil-water availability related to less rainfall as well as its high rainfall variability during dry season (coefficient of variation = 133%). Yields of potato for planting times December-January, April-May and August-September were (21.4 + 3.4), (20.5 + 3.5) and (16.9 + 2.2) tonnes/ha, respectively.